(untitled) (Bangladesh Medical Journal, 2017)
Dealing with different toxic chemical and physical agents in ship scrapping activities of ship breaking workers make them vulnerable to suffer from different occupational health hazards including skin diseases. this cross sectional study was carried out in Bangabandhu Sheikh Mujib Medical University, Dhaka and a temporary health center established near the ship-breaking yards of Shitakunda, Chittagong to describe the frequency and pattern of skin diseases among ship-breaking workers in Bangladesh. Five hundred workers of ship breaking yards were included consecutively, history was taken and examined to diagnose skin diseases. Physical examination and laboratory tests (patch test, prick test, woods lamp test, microscopy and histopathology) were done where needed. Most (69.2%) of the workers were from the age group 15 to 62 years and 27.8% were <18 years. Only 27 (5.4%) had some sorts of training and 24.8% do not use any type of protective measure. At least one form of skin disease was found in 47.8% workers. Types of skin diseases were contact dermatitis (19.4%), scabies (15.8%), accidental cut/burn/scald (15.6%), fungal infection (dermatophytosis / pityriasis versicolor/ candidiasis) (10.6%), impetigo / pyoderma (9.8%), seborrheic dermatitis (9.6%), acne 7.2%, palmoplantar keratoderma 4.8%, glossitis/stomatitis/ chelitis 4.4%, lichen simplex chronicus 3.4%, urticaria 2.4% and psoriasis 1.2%. Contact dermatitis, scabies, accidental cut/burn/scald, fungal infections, impetigo/pyoderma, seborrheic dermatitis and acne are the common skin diseases among ship breaking workers. Ensuring adequate protective measures, awareness and training can control these skin diseases among ship-breaking workers. Bangladesh Med J. 2016 Sep; 45 (3): 147-150